2011
DOI: 10.1089/fpd.2011.0901
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Radish and Alfalfa Seeds Inoculated withEscherichia coliO157:H7 andSalmonellaby a Gaseous Acetic Acid Treatment

Abstract: The majority of seed sprout-related outbreaks have been associated with Escherichia coli O157:H7 and Salmonella. Therefore, we aimed to find an effective method to inactivate these organisms on seeds before sprouting. Treatment with 8.7% (v/v) acetic acid at 55°C for 2-3 h reduced the population of E. coli O157:H7 and Salmonella inoculated on alfalfa (Medicago sativa L.) and radish seeds (Raphanus sativus L.) by more than 5.0 log CFU/g, and a longer treatment time completely eliminated the E. coli O157:H7 popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Previous studies have indicated the effectiveness of gaseous acetic acid to inactivate E. coli and Salmonella in alfalfa seeds (Medicago sativa L.) and radish seeds (Raphanus sativus L.) (Nei et al, 2011(Nei et al, , 2014. In addition, other research groups reported high bactericidal effects of gaseous acetic acid on Salmonella and E. coli O157:H7 inoculated on mung bean seeds (Delaquis et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated the effectiveness of gaseous acetic acid to inactivate E. coli and Salmonella in alfalfa seeds (Medicago sativa L.) and radish seeds (Raphanus sativus L.) (Nei et al, 2011(Nei et al, , 2014. In addition, other research groups reported high bactericidal effects of gaseous acetic acid on Salmonella and E. coli O157:H7 inoculated on mung bean seeds (Delaquis et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Within individual rows, the values followed by different letters are significantly different (p < 0.05). by Delaquis et al (1999) and Nei et al (2011). Delaquis et al (1999) reported that 5.0e6.0 log reduction of E. coli O157:H7 and Salmonella inoculated on mung bean seeds was obtained by the gaseous acetic acid at 242 mL/L for 12 h at 45 C. Nei et al (2011) also indicated the more than 5.0 log CFU/g reduction of E. coli O157:H7 and Salmonella inoculated on alfalfa and radish seeds after the treatment with 8.7% of gaseous acetic acid for 3e48 h at 55 C. On the other hand, Weissinger et al (2001) showed that the population of Salmonella was reduced from approximately 3.6 log CFU/g to 2.1 log CFU/g by the treatment at 50 C with 100e300 mg/L of gaseous acetic acid for 6 h. The lower reduction than that of the present study might be due to experimental conditions such as inoculation level, test strains and fumigation device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have published the methods how sprouts could be decontaminated and secure to eat (BAri et al, 2008(BAri et al, , 2009WAje et al, 2009;Nei et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of alfalfa and radish seeds with 8.7% acetic acid in the gaseous phase at 55°C for 3 h resulted in greater than 5-log reductions of E. coli 0157:H7 and Salmonella, with 96 to 98% germination (119). Malic acid is a low-cost, effective organic acid antimicrobial.…”
Section: Chemical Interventionsmentioning
confidence: 99%